An Anlysis Of Code Mixing On Social Media Networking Used By The Fourth Semester Students Of English Education Study Program Batanghari University In Academic Year 2017/2018 - Yessica Hosana Purba, Suyadi, Nurul Fitri (Universitas Batanghari Jambi, 2018)
AbstractCode mixing becomes phenomena of language. the code mixing can be applied among social interaction in bilingual. The aim of this Research is to provide a complete overview over the phenomenon of code mixing. The phenomenon in this research occur in social media. In this research, researcher presents why the strudents mix their language by status in social media. The researcher also match the type according what they in social media, The kind of research is qualitative research. The data are collected from WhatsApp, Instagram and Facebook status by screenshoot. The participant were fourth students class B English Education the Study Program Batanghari University Academic year 2018-2019. Students in the class fourth B there are 15 people. Sample from random sampling method. Method of collecting data used in this research are interview to get information arround their knowledge and reasons to use code mixing and documentation which is taken social media by screenshoot the status to be evidence. The result of this research shows that the most type they use is. Research also shows the result of the reasons is talking about particular topic as the highest result. This is showing that students potentially insert their words with foreign language expecially English.Keywords : Code Mixing, Social Media